Evaluation and Analysis of the Embodied Mind Perspective - Mohamad-Mahdi Moghadas; Ali Fath-Taheri; Abdul-Razzaq Hesamifar; Shirzad Peik-Herfeh (Journal of Philosophical Investigations)
This paper evaluates the embodied mind perspective in light of disembodied approaches to the mind. According to disembodied approaches, the body plays no fundamental role in constituting the mind. Mind and body are considered two distinct entities. This distinction is sometimes ontological and sometimes based on properties or characteristics. In these approaches, the body is described as a substrate, tool, neural realization, or container. In contrast, the embodied mind perspective argues that the mind is inherently embodied. The body constitutes the mind. Mind and body are not two distinct entities, but rather a single entity. Concepts, thoughts, emotions, and in sum, mental states and processes are fundamentally embodied. This means that the body plays a pivotal role in their formation. In this perspective, the body is the constitutive, not the substrate or tool. What supports this approach is a collection of empirical and cognitive findings. Based on these findings, the brain, body, and the surrounding environment together form a dynamic system, and mind and cognition are the consequences of this dynamic system. This approach is not merely about description or explanation; rather, the embodied mind is the outcome of an interdisciplinary approach that is supported by numerous empirical findings. However, this approach is not without its criticisms. The most prominent critiques highlight several key issues, including ambiguities in its fundamental principles, a lack of empirical evidence, insufficient consideration of higher-order cognitive processes, and the reductionist tendency to reduce all mental states to physical states. In this paper, we seek to critically analyze and evaluate this perspective, examining its theoretical underpinnings within the broader academic discourse.